The multifaceted role of quaking protein in neuropsychiatric disorders and tumor progression - Guo, Zeshang; Liu, Bo; Wei, Ying; Wang, HeFei; Zhang, Qingquan; Hong, Xinyu (Frontiers in Neuroscience, 2024)
The Quaking protein (QKI) belongs to the STAR protein family and plays a significant role in the development of the nervous system. It serves as a crucial regulator in the processes of tumor progression and cardiovascular system development. Within the central nervous system, QKI has been associated with the onset and progression of numerous neuropsychiatric disorders, including schizophrenia, depression, ataxia, and Alzheimer's disease. In malignant tumors, the methylation of the QKI promoter inhibits its expression. QKI primarily involves in the generation, stability, and selective splicing of non-coding RNA, as well as in mRNA translation. The role of QKI in the tumor microenvironment should not be overlooked. Especially in Glioblastoma Multiforme (GBM), although QKI is not the primary mutation, it still plays a vital role in maintaining the stemness of GBM.However, the mechanisms and further studies on this topic demand extensive basic and clinical trials. signaling pathways. MYB: QKI fusion is commonly observed in AG (Astrocytoma Grade).